Behaviour change intervention to reduce caregivers’ exposure to patients’ oral and nasal secretions in Bangladesh - Gurley, Emily S; Islam, M. Saiful; Nahar, Nazmun; Sultana, Rebeca; Hossain, M. Jahangir; Homaira, Nusrat; Parveen, Shahana; Naushin, Tania; Alam, Mahbub-ul; Khan, AKM Dawlat; et al. (International Journal of Infection Control, 2013)
Family caregivers are at risk for acquiring Nipah virus from patients in Bangladesh through exposure to patients’ respiratory secretions. We conducted a formative study to assess the acceptability and feasibility of behaviour change messages to reduce this exposure in a hospital in Bangladesh. We delivered a bar of soap with behaviour change messages to caregivers asking them to: 1) wash hands with soap at key times; 2) not eat patient’s leftover food; 3) sleep with their back to the patient or with the patient’s face to their chest; and 4) maintain more than one hand’s distance between patient’s and caregiver’s faces. Structured observations and semi-structured interviews with caregivers were used to assess acceptability and feasibility. Caregivers of 15 patients were enrolled. We observed an opportunity for caregiver handwashing 172 times, and in 20 (12%) of these opportunities caregivers washed hands with soap. Caregivers cited an inability to leave a severely ill patient unattended and lack of access to water as barriers to handwashing. Caregivers abstained from sharing food with patients in 82% (61/74) of observations with an opportunity to do so, and followed our sleeping suggestions in 88% (113/128). In only 12% (40/336) of observation sessions did the caregiver keep their face more than one hand’s distance from the patient’s. Behavioral messages regarding sleeping position and food-sharing were both acceptable and feasible; maintaining a distance from the patient was neither. Handwashing was acceptable, but not feasible. Interventions to target this at-risk group should include improved access to handwashing stations.